Islamophobia Never Rests in the Balkans: Muslim Communities and the Legacy of Exclusionary Nationalisms and Ethnic Expulsions. Issue 3 (3rd July 2019) - Taras, Raymond
Abstract: A long history of anti-Muslim prejudice has marked the Balkans. From Pope Urban's call to take the Holy Land back from the "Turks, " to the writings of Martin Luther seeking repentance for Christian sins by undergoing Muslim persecution, to anti-Ottoman invectives by Catholic writers in the sixteenth century, Islamophobia has been a dominant narrative. But Islamophobic Orientalism may be a preferred framework for examining anti-Muslim prejudice since the intersectionality of race and religion, combined with region, offers a more comprehensive explanatory narrative. Over la longue durée ["the long term"], the crumbing of Islamic structures in the late nineteenth century, the horrors of World War II on the peninsula, and the outbreak of the Balkan wars in the 1990s—with genocide charges invoked as the definitive sanction—sapped the Muslim presence. The refugee crisis affecting the Balkans contributed further to producing internally-displaced persons and others seeking protection abroad. Albanian writer Ismail Kadare serves as source conveying the exclusionary character of nationalism, prejudice, and stereotyping for a region abounding in provincial, ethnic, and religious intermingling.